A teachers’ based approach to assessing the perception of critical thinking in Education university students based on their age and gender - Galindo-Domínguez, Héctor; Bezanilla, María-José; Campo, Lucía; Fernández-Nogueira, Donna; Poblete, Manuel (Frontiers in Education, 2023)
In the 21st century, critical thinking (CT) is regularly presented as one of the most important competences to be developed by a majority of educational institutions. Teachers are expected to change and enrich their teaching and learning methodologies so that students could face future challenges. Nonetheless, few are the instruments that measure the perception of critical thinking based on teachers’ conception. The aim of this study is to design and validate an instrument for the assessment of CT in university students based on the conception of CT that university teachers have. For this study, a total of 312 Spanish university students have participated. Based on a good model fit from a Confirmatory Factor Analysis and good reliability indices, the results provide strength to the theoretical model to evaluate critical thinking in university students formed by 6 dimensions (Analyzing/Organizing; Reasoning/Argumenting; Questioning/Asking oneself; Evaluating; Positioning /Taking decisions, and Acting /Committing oneself) and 42 items. Similarly, age was not a predictor variable for the different dimensions; while gender was statistically in favor of women in some of the dimensions, and tendentially, the dimension of Positioning/Taking decisions, in favor of men. However, despite these differences, the model guaranteed its factorial invariance. These findings have important pedagogical implications for universities in particular, and educational institutions in general, when developing curricula and teaching plans that focus on the development of students' critical thinking.